2009
DOI: 10.2474/trol.4.42
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant Spin-off and Oxidation Phenomenon on Hard Disk Media

Abstract: High temperature (hot) and high humidity (wet) effects on perfluoropolyether lubricants, Z-dol and Z-tetraol, were investigated using the high speed spin-tester. The study has shown that: (1) higher humidity accelerates the lubricant spin-off on the disk surface, (2) in the case of Z-tetraol, oxidative reaction occurs under the hot-dry condition, but not under the hot-wet condition, (3) aforementioned phenomenon occurs only when the mobile fraction is present, and (4) the oxidation occurs the more strongly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…R = -CF 3 in the formula given above) are stable up to ~ 350 o C. The functional hydro-carbon end groups bring about chemical lability and lower thermal stability. Recently Wakabayashi reported on IR examination of disks coated with Z-dol and Z-tetraol, respectively, and spun in test stands for several months 1) . It was observed that the carbonyl band evolved with time on disks coated with Z-tetraol.…”
Section: Introductionmentioning
confidence: 99%
“…R = -CF 3 in the formula given above) are stable up to ~ 350 o C. The functional hydro-carbon end groups bring about chemical lability and lower thermal stability. Recently Wakabayashi reported on IR examination of disks coated with Z-dol and Z-tetraol, respectively, and spun in test stands for several months 1) . It was observed that the carbonyl band evolved with time on disks coated with Z-tetraol.…”
Section: Introductionmentioning
confidence: 99%